Tetanus Combined Immunization with Tetraxim and Pentaxim in Children from 3 Months to 4 Years - Alla Philippova (Journal of Global Pharma Technology, 2019)
The causative organism of tetanus is the Clostridium tetani. Immunization is one of the effective methods of disease prevention, which is carried out from the first 2 months of life. Further vaccination continues, in combination with the measles vaccine. Thus, tetanus in modern medicine is one of the elements of the combined vaccinations. 300 children were vaccinated hosted by the Department of Infectious Diseases of the Hospital № 2 in Moscow (Russian Federation) during the first six months of 2017. The age interval of children is from 3 months to 4 years. 2100 vaccinations were carried out, 1810 of which were vaccinations with Pentaxim, and the rest with Tetraxim. 255 children (85% of all), immunization program with Tetraxim was prolonged after the Pentaxim vaccinations. This is due to the fact that the first immunization occurs in half of a year. The reasons for this are in the social incompetency of the most parents as they begin immunization from 6 months, not from 3. The proposed drugs showed high-potency in children of different age groups and in state of health. Tetraxim and Pentaxim are applicable for children with allergies, as well as with CNS involvement. Moreover, they can be included in combination vaccines against such diseases as whooping cough, diphtheria, tetanus, poliomyelitis, Haemophilus influenzae b. It is due to the same components used, namely DTwP, IPV.